Aspek Yang Berpengaruh Terhadap Struktur Modal Pada Industri Makanan Dan Minuman Yang Tercatat Di Bursa Efek Indonesia Periode 2016-2018 - Umi Rahma Dhany; Febri Suaida Rosalinawati; Joni Hendra (Fakultas Ekonomi Universitas Panca Marga, 2021)
The research was conducted at Food and Beverage Companies listed on the Indonesia Stock Exchange for the period 2016-2018 with the aim of knowing the factors that influence capital structureThis research uses associative research. The sample of this study was determined by purposive sampling method based on criteria. Data analysis method in the form of multiple linear regression analysis. The results showed that simultaneously it can be seen that the variables Business Risk, Asset Structure, and Firm Size simultaneously have a significant effect on the Capital Structure as evidenced by the value of Fcount > Ftable with a significant level α = 0.05, partially the Business Risk variable has no significant effect on Capital Structure, while the Asset Structure and Company Size variables have a significant positive effect on Capital Structure as evidenced by t count > t table.